Thermal regime of enclosing structures - Shahida Yesenbekovna Shonbasova; Guldana Soltanovna Abieva (Scientific Research and Experimental Development, 2024)
It is known that there is a direct relationship between the population density of cities and the cost of energy conservation, which stimulates the construction of high-rise buildings, high-rise buildings. At the same time, special attention is paid to the development of the concept of an "energy-efficient house" with increased comfort in the premises of buildings and energy savings. And this requires new solutions for thermal protection of buildings and heating, ventilation and air conditioning systems that determine their thermal regime. The main purpose of the building is to protect the people in it from the adverse effects of nature.